Penegakan Hukum Pelaku Tindak Pidana Penganiayaan Berat Karena Halusinasi di Kecamatan Satarmese Barat, Kabupaten Manggarai - Marselinus Mardi Anto; Aksi Sinurat; Rudepel Petrus Leo (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
The purpose of this study is to analyze the law enforcement of perpetrators of serious maltreatment due to hallucinations in Satarmese Barat Subdistrict, Manggarai Regency. This research is an empirical juridical research that examines a legal event that occurs through a statute cause approach. Data were collected in two ways, namely interviews and document studies. The data obtained is then presented descriptively qualitatively. The results showed that law enforcement of perpetrators of serious maltreatment due to hallucinations in West Satarmese District, Manggarai Regency in relation to liability that the perpetrators were released from criminal liability by investigators which was not in accordance with Article 44 of the Criminal Code and termination of investigation which was not in accordance with the provisions of Article 109 of the Criminal Procedure Code. The obstacles to law enforcement are influenced by several factors, namely: facilities and infrastructure factors (limited facilities and infrastructure available at Satarmese Police Station), law enforcement factors (inconsistency of investigators with existing regulations), community factors (lack of understanding of community law), and cultural factors (Manggarai community culture is thick with kedi kilo (kinship) in solving problems.